The Influence of Demographic Transition, Education, Number of Industries, and Covid-19 on Unemployment in the 2018-2022 Period (A Case Study of 38 Regencies and Cities in East Java) - Ananta, Hadyan Arya; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Unemployment is one of the macroeconomic problems that is very difficult to overcome. In the period 2018 to 2023, the open unemployment rate in East Java Province soared due to the Covid-19 outbreak. In 2023, the open unemployment rate in East Java decreased. Despite the decrease from the previous year, the unemployment rate in East Java is still far from the ideal level. This is caused by various factors, such as the high growth of the labor force, the mismatch of skills with the needs of the job market, and others. This study aims to analyze the causes of the high unemployment rate in East Java Province and the efforts to overcome it. The data used is secondary data of 38 districts/cities in East Java Province which is then processed with panel data regression analysis method. The analysis shows that demographic transition and number of industries have a significant negative effect on unemployment in East Java. In contrast, education has a positive and significant effect on unemployment. This shows that the potential demographic bonus in East Java is well realized, especially when the labor market can absorb the growth of the labor force. Meanwhile, the high average length of schooling does not necessarily reflect the quality of educators or the suitability with the needs of the labor market.